2008
DOI: 10.1155/2008/706240
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Uranium and Rare Earth Elements Using Biomass of Algae

Abstract: In order to investigate the behavior of rare earth elements (REEs) and uranium (U) in marine organism, the concentrations of REEs and U in some brown algae samples taken on the coast of Niigata Prefecture were determined. In addition, laboratory model experiment to uptake these elements using living and dried algae (Undaria pinnatifida and Sargassum hemiphyllum) was also carried out to survey the uptake and bioaccumulation mechanism of REEs and U in algae. Consequently, the following matters have been mainly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 26 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…Previous studies have shown that the concentration factor of biomass such as algae for uranium in seawater is about 200 (18), which is too low for practical applications. Development of Innovative biomaterials with engineered protein (such as that shown in Figure 12 could significantly increase the concentration factor and make bio-collection practical.…”
Section: Developing New Materials To Improve the Chemical Stability mentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown that the concentration factor of biomass such as algae for uranium in seawater is about 200 (18), which is too low for practical applications. Development of Innovative biomaterials with engineered protein (such as that shown in Figure 12 could significantly increase the concentration factor and make bio-collection practical.…”
Section: Developing New Materials To Improve the Chemical Stability mentioning
confidence: 98%
“…The laboratory studies cover the preparation of amidoxime-based adsorbents, the equilibrium of the uranium uptake, and the kinetics and mechanism of the extraction of uranium from seawater (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Collection of uranium with chitosan-resin and biomass such as algae was also performed (17,18). The marine experiments were performed by using two types of collection systems: the stack system and the braid system (19,20).…”
Section: Recent Studiesmentioning
confidence: 99%
“…Golenkinia sp . Ulva innatifida Sargassum hemiphyllum Biosorption Biosorption Biosorption Biosorption Biosorption Biosorption Biosorption Biosorption Biosorption Bioaccumulation Bioaccumulation batch, 45 min, pH4, pH5 batch, 5 h, pH6 batch, 5 h, pH6 batch, 6 h, pH6 batch, 5 h, pH6 batch, 5 h, pH6 batch, 5 h, pH6 batch, 8 h, 23 °CC, pH7.5 batch, 8 h, 23 °CC, pH7.5 batch, 1.25d, 15 °CC, pH3 batch, 1.25d, 15 °CC, pH3 Palmieri et al ( 2001 ) Birungi and Chirwa ( 2013 ) Birungi and Chirwa ( 2014 ) Correa et al ( 2016 ) Sakamoto et al ( 2008 ) Eu Acutodesmus acuminutus Biosorption batch, 40 °CC, pH4, pH7 Furuhashi et al ( 2019 ) Nd, Eu Chlorella brevissima Chlorella kessleri Calothrix brevissima Biosorption Biosorption Biosorption batch, RT, 25 °CC, 60, 80, 100 µmol/s/m 2 batch, RT, 25 °CC, 60, 80, 100 µmol/s/m 2 batch, RT, 25 °CC, 60, 80, 100 µmol/s/m 2 Heilmann et al ( 2021 ) Pr Turbinaria conoides Sargassum wightii Biosorption Biosorption batch, 1 h, pH5 batch, 1 h, pH5 Vijayaraghava and Jegan ( 2015 ) La, Nd, Dy; Y, Sm; Ce, Eu, Tb Galdieria sulphuraria Bioaccumulation Bioaccumulation Bioaccumulation batch, 0.5d, 42 °CC, pH1.5 batch, 45 °CC, pH3 batch, 1d, 37 °CC, pH2.5–5.5, 50 µmol/s/m 2 Minoda et al ( 2015 ) Sun et al ( 2022 ) Iovinella et al ( 2022 ) Sc, REE Posidonia oceanica …”
Section: Algaementioning
confidence: 99%
“…Plants and aquatic organisms have been reported to accumulate U from soils and water in the range of 0.08-3500 mg kg −1 (Huang et al, 1998;Dienemann et al, Frontiers in Environmental Science frontiersin.org Chang et al, 2005;Sakamoto et al, 2008;Viehweger and Geipel, 2010;Caldwell et al, 2012;Cordeiro et al, 2016;Boryło et al, 2017;Li C et al, 2019;Bergmann and Graca, 2020). Hyperaccumulation of U from contaminated sites has been reported for several plant species and aquatic organisms (Dienemann et al, 2002;Chang et al, 2005;Viehweger and Geipel, 2010;Caldwell et al, 2012;Li C et al, 2019;Bergmann and Graca, 2020).…”
Section: Biota Accumulationmentioning
confidence: 99%